Selectivity in the impact of P‐glycoprotein upon pulmonary absorption of airway‐dosed substrates: A study in ex vivo lung models using chemical inhibition and genetic knockout1. Issue 9 (13th May 2013) - Al‐Jayyoussi, Ghaith; Price, Daniel F.; Francombe, Danielle; Taylor, Glyn; Smith, Mathew W.; Morris, Chris; Edwards, Chris D.; Eddershaw, Peter; Gumbleton, Mark; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; et al.
Abstract P‐glycoprotein (P‐gp) mediated efflux is recognised to alter the absorption and disposition of a diverse range of substrates. Despite evidence showing the presence of P‐gp within the lung, relatively little is known about the transporter's effect upon the absorption and distribution of drugs delivered via the pulmonary route. Here, we present data from an intact isolated rat lung model, alongside two isolated mouse lung models using either chemical or genetic inhibition of P‐gp. Data from all three models show inhibition of P‐gp increases the extent of absorption of a subset of P‐gp substrates (e.g. rhodamine 123 and loperamide) whose physico‐chemical properties are distinct from those whose pulmonary absorption remained unaffected (e.g. digoxin and saquinavir). This is the first study showing direct evidence of P‐gp mediated efflux within an intact lung, a finding that should warrant consideration as part of respiratory drug discovery and development as well as in the understanding of pulmonary pharmacokinetic (PK)‐pharmacodynamic (PD) relationships. © 2013 Crown copyright. 102:3382–3394, 2013